Hubungan antara Kemampuan Mengunyah Makanan dengan Kemampuan Artikulasi pada Anak Down Syndrome di Samarinda - Siti Nurhalisyah Siti; Sudarman Sudarman (Jurnal Terapi Wicara dan Bahasa, 2023)
Background:Skills in the process of eating will develop from an early age and allow for textural transitions that start from accepting a single texture into a variety of textures. Chewing problems are usually caused by abnormalities in the organs involved in the chewing process. Chewing activities involve good cooperation between the muscles of the face, lips, jaw and tongue, where the neuromotor function also help in clarity of articulation (Ganny, 2021) Purpose:This study aims to determine the relationship between the ability to chew food with articulation skills in children down syndrome in Samarinda Method:This research is quantitative by design correlation research. A sample of 33 samples based on inclusion criteria. Sampling technique viz cluster sampling with statistical tests using contingency coefficient Thesis Results:There is a relationship between the ability to chew food with articulation skills in children with Down syndrome in Samarinda. The result of the contingency correlation test was 0.009 <0.05 so that H0 was rejected and Ha was accepted. The correlation value is .416, the strength of the relationship is moderate/sufficient and the direction of the correlation is positive. Conclusion:There is a relationship between the ability to chew food with articulation skills in children down syndrome in Samarinda